Development of Gymnastics Learning Media based Android - Fegie Rizkia Mulyana; Ridwan Gumilar; Novi Soraya (Universitas PGRI Palembang, 2022)
This study aims to develop and produce products in the form of gymnastics learning media based on android applications. This study uses research and development research methods with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluations). The research carried out only reached the development or development stage, because this research only developed and produced an android application-based gymnastics learning media product called